Analysing the impact of dependency on conditional survival functions using copulas - Hadi Safari-Katesari; Samira Zaroudi (Statistics in Transition New Series, 2021)
Nowadays, insurance contract reserves for coupled lives are considered jointly, which has a significant influence on the process of determining actuarial reserves. In this paper, conditional survival distributions of life insurance reserves are computed using copulas. Subsequently, the results are compared with an independence case. These calculations are based on selected Archimedean copulas and apply when the "death of one individual" condition exists. The estimation outcome indicates that the insurer reserves calculated by means of Archimedean copulas are far more effective than those resulting from an independence assumption. The study demonstrates that copula-based dependency modelling improves the calculations of reserves made for actuarial purposes.
Keywords: 519; conditional survival distribution; copula; Kendall’ s tau; reserves; life table